2011
DOI: 10.4236/fns.2011.25058
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Raw Milk Quality in Kosovo

Abstract: In Kosovo, a new regulation on quality standards and grade of fresh milk is valid since January 1, 2007. The regulation was based on the respective EU-regulation and has an ambitious time frame with a transition period of only three years. In order to estimate the impact of this new regulation, a survey on the quality of raw milk delivered to the Kosovar dairies was carried out from January to May 2007. The aim was to get a reliable picture of the current raw milk quality in the dairy channel in Kosovo, to dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Previous studies conducted on the quality of fresh milk in Kosovo have shown high CFU and SCC values, indicating high level of contamination during milking and storage of milk after milking (Bytyqi et al, 2010). About 24% of milk collected was evaluated as being of poor hygiene, depicting values of more than 500,000 SCC cells/mL and around 50% of the samples had more than 3,000,000 CFU/mL of milk in a study carried out with dairy farms in Kosovo (Bytyqi et al, 2011). The enforcement of the quality standard without intervention in milk preservation and handling infrastructure would take out of business about 90% of the dairy farmers who deliver the milk to the dairies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted on the quality of fresh milk in Kosovo have shown high CFU and SCC values, indicating high level of contamination during milking and storage of milk after milking (Bytyqi et al, 2010). About 24% of milk collected was evaluated as being of poor hygiene, depicting values of more than 500,000 SCC cells/mL and around 50% of the samples had more than 3,000,000 CFU/mL of milk in a study carried out with dairy farms in Kosovo (Bytyqi et al, 2011). The enforcement of the quality standard without intervention in milk preservation and handling infrastructure would take out of business about 90% of the dairy farmers who deliver the milk to the dairies.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, regarding bacterial contamination (CFU), the practices and conditions under which small-scale farms and their dairy chains operate make it difficult to produce high quality milk. For SCC, as in the [19], the results obtained that the amount of somatic cells (SCC) in fresh milk from the small-scale dairy farms is relatively acceptable according to the standard in the country. However, there are a lot of variation deriving from different farms (CP) indicating the large managerial divergence, breeds impact, farm infrastructure, and the present structure of animal health control in the country [1].…”
Section: Discussionmentioning
confidence: 99%
“…Author(s) agree that this article remains permanently open access under the terms of the Creative Commons Attribution License 4.0 International License Bytyqi et al, 2011). Several studies have reported the presence of both gram positive and gram negative pathogens in the dairy industry (Amagliani et al, 2012;De Vliegher et al, 2012;Gurol et al, 2012;Lee et al, 2012Lee et al, , 2014Ranieri et al, 2012;Barancelli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%